PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PENYELESAIAN SOAL CERITA PECAHAN - Rahmawati, Rahmawati; Arlis, Syamsu; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
THE EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL ON RESOLVING ABILITY OF STORY BASED FRACTION QUESTIONThe aim of this study is to determine the effect of the Problem Based Learning (PBL) model on resolving ability of  story based Fraction question in fifth grade of  elementary school students. This type of research is a quasi-experimental study. The samples of this study were the fifth grade students of SDN 13 Salimpaung and the fifth grade students of SDN 03 Salimpaung. Based on the results of  the research which obtained by  using t-test, obtained the results of tcount is 2.965  and ttable is 2.015 at the significance level α = 0.05, so that can be conclude that t count > t table. This shows there is a significant effect on the application of the PBL model on the story-based addition and subtraction fraction questions  in class V of SDN Gugus III in Salimpaung District.  Keywords : PBL Model , Mathematics, Resolving Ability of Story-Based Questions